Analysis of gene expression difference and biological process in chorionic villi of unexplained recurrent spontaneous abortion - Linling Shi; Lun Wei; Meiqiu Lu; Hongmei Ding; Le Bo (BMC Pregnancy and Childbirth)
Abstract Objective To explore the biological relationship between the regulatory signal pathways involved in differentially expressed genes and recurrent spontaneous abortion (RSA) by analyzing the gene expression microarray data of unexplained RSA. Methods The gene expression profile data of chorionic villi from unexplained recurrent abortion with normal karyotype and selective induced abortion were compared. Differentially expressed genes were analyzed by the “Limma” package in R Studio, and Gene Ontology(GO) and Kyoto Encyclopedia of Genes and Genomes(KEGG) pathway enrichment analysis were carried out with “Cluster Profiler” and “org.hs.eg.db” packages. Finally, hub genes were identified through constructing the protein-protein interaction (PPI) network from the differentially expressed gene dataset in the STRING database. And the hub genes were verified by RT-PCR. The expression of TH1 and TH2 cytokines representing IL-2, IL-10 and their receptors related to hub gene immune regulation were detected by enzyme-linked immunosorbent assay (ELISA) and western blot (WB), respectively. Results A total of 295 differentially expressed genes were identified in the dataset GSE22490, with a significance level of P < 0.05 and an absolute log-fold change > 1.0, which included 166 up-regulated genes and 129 down-regulated genes. Go and KEGG enrichment analysis of these differentially expressed genes (P < 0.05,FDR < 0.05) revealed significant involvement in the regulation of inflammatory and immune responses. The PPI analysis revealed that the hub genes FCGR3A, TLR2, BTK, CLEC7A and CD163 were centrally located in the network cluster which were composed of the proteins encoded by differentially expressed genes associated with RSA. The mRNA levels of FCGR3A, TLR2 and CLEC7A in the RSA group were significantly higher than those in the NC group (P < 0.05). The protein expression level of TLR2 was also significantly increased in the RSA group (P < 0.05). The level of IL-2 in the RSA group was significantly higher than that in the NC group (P < 0.05), while the protein expression level of its receptor was not different(P > 0.05). There was no significant difference in the expression levels of IL-10 and its receptor between the two groups (P > 0.05). Conclusion Abnormal immune response plays an important role in unexplained RSA. The imbalance in immune regulation may be one of the most important reasons behind this phenomenon. These findings provide a foundation for further research into the mechanisms underlying RSA.